Sekularisme Ataturk: “Madaniyah” atau “Lā Dῑniyah”? (Tipologi Sekularisme Ataturk ) (State Islamic Institute of Kudus (IAIN Kudus), 2019)
This article outlines the question whether Ataturk's secularism has the dimension of abolition of religion (lā dῑniyah) as assumed by many people or has the dimension of state domination over religion which is an expression of nationalism? This is because most classical Islamic political thinkers view that the relationship between religion and state is an organic unity, which cannot be separated from one another. The institutional form for the organic relationship arises in the form of a khilafah. These conditions describe the relationship between politics or power and religion as a symbiotic relationship that is mutually beneficial. As Europeans entered the Middle East, modern thoughts in the region also entered, one of which was kemalism. It was with this understanding that Ataturk in Turkey shocked the Islamic political world by displacing the already weak Ottoman Caliphate. The ideology of kemalism is caused by Ataturk actually a nationalist who admires the west, who wants the progress of Islam, therefore, according to him, it needs to be renewed in matters of religion to suit the Turkish soil. Thus, the practice of secularism in Turkey, broadly, belongs to the category of semi-secular practice, or typology of differential secularism, or